China versus the US who will prevail? - Toro Hardy, Alfredo 1950- (World Scientific, 2020)
The heralding of ambitions and hardening of geopolitical and military stances by China has given rise to few questions: Did China challenge the United States too hard and too soon and, by doing so, seriously jeopardize its chances of achieving its objectives? Can Washington still contain China's ascendancy and retain its current leading status?This book attempts to explore these questions and analyse if China has tried to display its strength to America too soon. It argues that by comparing the comprehensive national power of the two countries, one may be able to answer the above questions.List of author features on the book: for an Author Interview with the Global Labor Organization.